Human iPSC–Derived Endothelial Cells Exhibit Reduced Immunogenicity in Comparison With Human Primary Endothelial Cells - Haiyan Jia; Melanie Moore; Meenu Wadhwa; Chris Burns (Stem Cells International)
Human induced pluripotent stem cell (iPSC)–derived endothelial cells (ECs) have emerged as a promising source of autologous cells with great potential to produce novel cell therapy for ischemic vascular diseases. However, their clinical application still faces numerous challenges including safety concerns such as the potential aberrant immunogenicity derived from the reprogramming process. This study investigated immunological phenotypes of iPSC-ECs by a side-by-side comparison with primary human umbilical vein ECs (HUVECs). Three types of human iPSC-ECs, NIBSC8-EC generated in house and two commercial iPSC-ECs, alongside HUVECs, were examined for surface expression of proteins of immune relevance under resting conditions and after cytokine activation. All iPSC-EC populations failed to express major histocompatibility complex (MHC) Class II on their surface following interferon-gamma (IFN-γ) treatment but showed similar basal and IFN-γ-stimulated expression levels of MHC Class I of HUVECs. Multiple iPSC-ECs also retained constitutive and tumor necrosis factor-alpha (TNF-α)-stimulated expression levels of intercellular adhesion molecule-1 (ICAM-1) like HUVECs. However, TNF-α induced a differential expression of E-selectin and vascular cell adhesion molecule-1 (VCAM-1) on iPSC-ECs. Furthermore, real-time monitoring of proliferation of human peripheral blood mononuclear cells (PBMCs) cocultured on an endothelial monolayer over 5 days showed that iPSC-ECs provoked distinct dynamics of PBMC proliferation, which was generally decreased in alloreactivity and IFN-γ-stimulated proliferation of PBMCs compared with HUVECs. Consistently, in the conventional mixed lymphocyte reaction (MLR), the proliferation of total CD3+ and CD4+ T cells after 5-day cocultures with multiple iPSC-EC populations was largely reduced compared to HUVECs. Last, multiple iPSC-EC cocultures secreted lower levels of proinflammatory cytokines than HUVEC cocultures. Collectively, iPSC-ECs manifested many similarities, but also some disparities with a generally weaker inflammatory immune response than primary ECs, indicating that iPSC-ECs may possibly exhibit hypoimmunogenicity corresponding with less risk of immune rejection in a transplant setting, which is important for safe and effective cell therapies.